2023
DOI: 10.1088/0256-307x/40/5/057404
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity Observed in Tantalum Polyhydride at High Pressure

Abstract: We here report experimental discovery of tantalum polyhydride superconductor. It was synthesized at high pressure and high temperature conditions using diamond anvil cell combined with in-situ high pressure laser heating techniques. The superconductivity was investigated via resistance measurements at pressures. The highest superconducting transition temperature T c was found to be ~30 K at 197 GPa in the sample that was synthesized at the same pressure with ~2000 K heating. The transitions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The synthesis can only be carried out with high laser power that frequently damages the anvils. This prevents us from further increasing or releasing pressure to study the pressure dependence of SC as we have performed for other polyhydride superconductor studies [ 18 , 26 ]. The zero resistance at zero field is suppressed by applying a magnetic field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis can only be carried out with high laser power that frequently damages the anvils. This prevents us from further increasing or releasing pressure to study the pressure dependence of SC as we have performed for other polyhydride superconductor studies [ 18 , 26 ]. The zero resistance at zero field is suppressed by applying a magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…For the heavy rare earth elements with f shell fully filled, the lutetium hydride of Lu 4 H 23 was reported to exhibit SC with T c = 71 K at 218 GPa [ 21 ]. The hydrides of IVB and VB group metal of Zr, Hf and Ta were found to host SC at megabar pressure with T c = 71 K [ 22 ], 83 K [ 23 ] and 30 K [ 26 ], respectively. Most discovered binary hydride superconductors are found to be located in group IIA and IIIB in the periodic table and have electronegative values smaller than 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…This research field represents one of the most fascinating scientific and technological explorations in modern condensed-matter physics. In this area of research, advanced first-principles calculations [2][3][4][5][6][7][8][9][10][11] are essential parts of the experimental quest for the discovery of new hydrides phases [12][13][14][15][16][17][18][19][20][21], and both of these directions drive the development of new experimental techniques with which to study highly pressurized materials [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…From 2015 until now, several dozen high-temperature superconducting polyhydride phases have been discovered and studied [1,[12][13][14][15][16][17][18][19][20][21]24,[32][33][34][35][36][37][38][39][40][41][42][43][44][45]. At the same time, highpressure studies of superconductivity and high-pressure material synthesis [46][47][48] in nonhydrides (including cuprates [49][50][51][52]) have also progressed [53][54][55][56][57][58][59][60][61][62], including the observation of T c > 26 K in highly compressed elemental titanium [63,64] and scandium [65,66], and the discovery that T onset c ∼ = 78 K [67,68] and T zero c ∼ = 45 K [69]…”
Section: Introductionmentioning
confidence: 99%
“…[21] With the advancement of preparation technology and scientific research, an increasing number of innovative fabrication methods are being continuously developed and refined, among which high-pressure technology has been proved as a novel approach in manipulating the properties of materials. [22][23][24] The approach offers the advantages of rapid synthesis, a straightforward preparation process, and the enhancement of various material properties through tuning the geometry and electronic structures. [25][26][27] Jia et al revealed that under high pressure (5.2 GPa), the carrier concentration of PbTe is more than ten times of † These authors contributed equally to this work.…”
mentioning
confidence: 99%